Impact of depression and fatigue on relapsing remitting multiple sclerosis in Kingdom of Saudi Arabia - Alshamrani, Foziah J. (Saudi Med J, 2020)
OBJECTIVES: To determine relationship between fatigue, depression with the registration in multiple sclerosis (MS) society activity, and stress with the risk developing a new attack in patients with Relapsing remitting MS (RRMS) in the Kingdom of Saudi Arabia (KSA). METHODS: This was a cohort retrospective study conducted in the KSA between July 2018 and July 2019 which included a total of 465 RRMS patients. Data were collected during interviews using the Beck Depression Inventory (BDI) and Modified Fatigue Impacts Scale (MFIS). Demographic and clinical data were also collected. RESULTS: Of 465 participants, 317 expressed psychological stress before the last attack, 67 of whom developed an attack within 4 weeks, and 250 of whom developed an attack after 4 weeks. Significantly lower BDI scores were associated with registration in MS associations (p=0.003, df = 5). Significantly lower MFIS scores were associated with registration in MS associations (p=0.001, df = 5). CONCLUSION: The majority of RRMS patients have a significant fatigue and depression, and there are significant relationships between registration in the MS society and MFIS and BDI scores where patients who officially registered in MS society have lower score in MFIS and BDI. we recommend regular follow-ups with a psychologist and/or registration with MS societies.